2008
DOI: 10.1007/s11270-008-9906-6
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost for Tinted Organic Cationic Dyes Retention

Abstract: The use of vermicompost was expanded as natural adsorbent for cationic dyes retention. The adsorption profiles in batch and flow modes for crystal violet and methylene blue on vermicompost material were evaluated. In batch mode, a retention index higher than 97% was obtained for both compounds, while in flow condition, 40 g of dried adsorbent material were enough to remove 100 mg of crystal violet or methylene blue at column flow rates of 5 and 20 mL min −1 . Adsorption isotherms showed adsorptive maximum capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…As shown in the figure, the peak of Fe-BC3 is more intense at the same wavenumber than that of BC3, which indicates the formation of compounds with stronger bonds for the former biochar. The broad and less intense absorption peaks at 3415 cm −1 are mainly due to the vibration of –NH and –OH contained in amines, amides, alcohols, phenols and so on [19]. The symmetric and antisymmetric vibrations of –CH 2 and –CH 3 on aliphatic hydrocarbons are mainly located between 2950 and 2850 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the figure, the peak of Fe-BC3 is more intense at the same wavenumber than that of BC3, which indicates the formation of compounds with stronger bonds for the former biochar. The broad and less intense absorption peaks at 3415 cm −1 are mainly due to the vibration of –NH and –OH contained in amines, amides, alcohols, phenols and so on [19]. The symmetric and antisymmetric vibrations of –CH 2 and –CH 3 on aliphatic hydrocarbons are mainly located between 2950 and 2850 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the removal process occurs rapidly: high removal percentages are generally reached within short contact times, in some cases of minutes. De Godoi Pereira et al (2009) observed quantitative retention of crystal violet onto a vermicompost after 10 minutes and of methylene blue after only one minute. Anastopoulos et al (2018) also observed maximum adsorption of methylene blue after one minute of contact.…”
Section: Dye Removal Capacity and Nature Of The Removal Processmentioning
confidence: 99%
“…Decoloration of effluents stained by cationic dyes (crystal violet and methylene blue) was achieved with the help of vermicompost (de Godoi Pereira, Korn, Santos, & Ramos, 2009). Because of the dyes' large spatial pores, a greater amount of adsorption occurred than is typically the case with natural dyes.…”
Section: Vermicompost In Wastewater Treatmentmentioning
confidence: 99%